Transnational Identity and Memory Making in the Lives of Iraqi Women in Diaspora, Nadia Jones-Gailani (2020). Issue 2 (1st October 2021) - Bellotta, Samanta
Review of: Transnational Identity and Memory Making in the Lives of Iraqi Women in Diaspora, Nadia Jones-Gailani (2020)Toronto, Buffalo and London: University of Toronto Press, 200 pp., ISBN 978-1-48750-316-1, h/bk, £44.55